Fluorescence fluctuation spectroscopy in reduced detection volumes. - Blom, H; Kastrup, L; Eggeling, C (2006)
Fluorescence fluctuation spectroscopy is a versatile technique applied to in vitro and in vivo investigations of biochemical processes such as interactions, mobilities or densities with high specifity and sensitivity. The prerequisite of this dynamical fluorescence technique is to have, at a time, only few fluorescent molecules in the detection volume in order to generate significant fluorescence fluctuations. For usual confocal fluorescence microscopy this amounts to a useful concentration in the nanomolar range. The concentration of many biomolecules in living cell or on cell membranes is, however, often quite high, usually in the micro- to the millimolar range. To allow fluctuation spectroscopy and track intracellular interaction or localization of single fluorescently labeled biomolecules in such crowded environments, development of detection volumes with nanoscale resolution is necessary. As diffraction prevents this in the case of light microscopy, new (non-invasive) optical concepts have been developed. In this mini-review article we present recent advancements, implemented to decrease the detection volume below that of normal fluorescence microscopy. Especially, their combination with fluorescence fluctuation spectroscopy is emphasized.